Thermal sensitive ceramic material with low resistance value and negative temperature coefficient and preparation method thereof
By using copper acetate, cobalt, nickel, manganese and oxalic acid as raw materials, combined with the replacement of Cu and Ni ions, a low resistance negative temperature coefficient thermosensitive ceramic material was prepared, which solved the problem of taking into account both stability and resistance values in the prior art. , realizes high stability and low resistance value ceramic material preparation, suitable for low temperature measurement and suppression of inrush current.
Patent Information
- Application Number
- CN202411336746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
It is difficult to take into account the stability and resistance value of the existing low resistance value negative temperature coefficient thermistor ceramic materials, and it is difficult to prepare materials with low resistance value and stability.
Copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid are used as raw materials to prepare spinel oxide powders through solid phase method, and Cu ions are used to replace Co ions, Ni ions are used to replace Mn ions, and bind to binders. Ceramic preparation, controlling the resistivity and stability of the material.
The prepared low resistance negative temperature coefficient thermosensitive ceramic material has good density, high stability and excellent conductivity. It is suitable for industrial production. The room temperature resistivity is between 28.0 and 993.8Ω·cm, and the B value is between 3056 and 3548K. The aging value is between 2.38% and 4.08%, which is suitable for low temperature measurement and suppression of inrush current.
Smart Images

Figure BDA0005058472530000031 
Figure BDA0005058472530000032
Abstract
Description
Technical Field
[0001] The invention relates to a negative temperature coefficient thermistor ceramic material with low resistance, high B value and high stability and a preparation method thereof, belonging to the technical field of negative temperature coefficient thermistor ceramic materials. Background Art
[0002] Negative temperature coefficient (NTC) thermistors have the characteristics of high temperature measurement accuracy, good interchangeability, and high reliability, and are widely used in temperature measurement, control, and compensation. Usually, NTC thermistor materials are composed of manganese transition metal spinel oxides with the general formula of AB2O4. With the development of science and technology, higher requirements are put forward for the low resistance and high B value of such materials. Usually, when the resistivity of the material is high, the B value is also high, and vice versa.
[0003] Studies have shown that in binary systems, the Cu-Mn-O series can achieve the lowest room temperature resistivity, but due to factors such as copper ion valence state transition and ion and vacancy migration, the electrical performance stability of this type of material is poor. Therefore, researchers hope to prepare high-quality low-resistance NTC thermistor ceramics by regulating the composition. For example, Cu 0.2 Ni 0.5 Mn 2.3 The room temperature resistivity of O4 ceramics is 70Ω·cm, and the aging value is 14.9%; Cu 0.2 Ni 0.66 Mn 2.14 The room temperature resistivity of O4 ceramics is 42Ω·cm, while the aging value is as high as 12.6%. In order to improve the stability of Cu-containing NTC thermistor ceramics, the addition of constant valence ions Zn 2+ However, although this method can increase the stability of the material, the room temperature resistivity of the material also increases. 0.2 Ni 0.66 Mn 2.14 Adding Zn to O4 ceramics 2+ , Zn 0.4 Cu 0.2 Ni 0.66 Mn 2.14 The aging value of O4 ceramics decreased to 4.2%, and the room temperature resistivity increased to 73.1Ω·cm. Furthermore, ZnCu 0.2 Ni 0.66 Mn 2.14 The aging value of O4 ceramics is reduced to 0.16%, and the room temperature resistivity is greatly increased to 980Ω·cm. It can be seen that it is difficult to prepare NTC thermistor ceramics with low resistance and good stability in the Cu-Mn-O and Cu-Ni-Mn-O series.
[0004] In addition, some researchers have conducted research on the Cu-Co-Mn-O system and found that Co0.98 Cu 0.4 Mn 1.62 The room temperature resistivity of O4 is 17.6Ω·cm, and the aging value is 2.38%. 0.98 Cu 0.5 Mn 1.52 The room temperature resistivity of O4 is 17.5Ω·cm, and the aging value is 2.68%. However, both materials are mixtures of cubic spinel and tetragonal spinel, and their uniformity and material interchangeability are difficult to guarantee. Therefore, for NTC thermistor ceramics with low resistance and high stability, new technical solutions need to be explored. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a low-resistance negative temperature coefficient thermistor ceramic material in view of the shortcomings of the existing low-resistance negative temperature coefficient thermistor ceramic material. The prepared negative temperature coefficient thermistor ceramic material has low resistance and high B value and high stability.
[0006] Technical Solution
[0007] The present invention discloses a method for preparing a low-resistance negative temperature coefficient thermistor ceramic material, comprising the following steps:
[0008] (1) mixing copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid uniformly to obtain a mixture, and then adding the mixture, a grinding medium and a dispersant into a ball mill to perform ball milling to obtain a mixed powder;
[0009] (2) drying the mixed powder, calcining it, cooling it, ball-milling it for the second time, drying it, and sieving it to obtain a powder;
[0010] (3) Adding a binder to the powder of step (2) to granulate, then performing compression molding, calcining the molded body, and finally cooling to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0011] Furthermore, in step (1), the amounts of copper acetate, cobalt acetate, nickel acetate and manganese acetate are measured in terms of metal atomic percentage, wherein the atomic percentage of copper is 6.67-10%, the atomic percentage of cobalt is 22.67-26%, the atomic percentage of nickel is 0-16.66%, and the atomic percentage of manganese is 50.67-67.33%, and the amount of oxalic acid is 1-1.5 times the total molar amount of metal atoms.
[0012] Furthermore, in step (1), the dispersant is anhydrous ethanol; and the weight ratio of the mixture, the grinding medium and the dispersant is 1:(1-3):(1-3).
[0013] Furthermore, in step (1), the rotation speed of the ball mill is 200 to 300 r / min, and the ball milling time is 3 to 12 h.
[0014] Furthermore, in step (2), the drying temperature is 80° C. and the drying time is 12 to 24 hours.
[0015] Furthermore, in step (2), the calcination temperature is 600-900° C. and the calcination time is 2-4 hours.
[0016] Furthermore, in step (2), the rotation speed of the secondary ball milling is 200 to 300 r / min, and the time is 6 to 24 h.
[0017] Furthermore, in step (2), the drying temperature is 80°C.
[0018] Furthermore, in step (3), the binder is a polyvinyl alcohol solution with a concentration of 5 to 8 wt%, and the mass ratio of the binder to the powder is (5 to 8): (92 to 95).
[0019] Furthermore, in step (3), the calcination temperature is 1000-1200° C. and the calcination time is 3-8 hours.
[0020] On the other hand, the present invention also discloses a low-resistance negative temperature coefficient thermistor ceramic material prepared by the above method.
[0021] Beneficial effects of the present invention:
[0022] The invention provides a method for preparing a low-resistance negative temperature coefficient thermistor ceramic material. The method uses copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid as raw materials, first prepares spinel structure oxide powder by a solid phase method, and then adopts a ceramic preparation process to prepare the negative temperature coefficient thermistor ceramic material, uses Cu ions to replace Co ions at the A position to reduce the resistivity of the system, and uses Ni ions to replace Mn ions at the B position. The strong coupling of Co and Ni controls the stability of the system. The method is simple to operate, and the prepared negative temperature coefficient thermistor ceramic material has the characteristics of good density, high stability, high precision, excellent conductivity, and suitability for industrial production. The room temperature resistivity is 28.0-993.8Ω·cm, the B value is 3056-3548K, and the aging value is 2.38%-4.08%, which is particularly suitable for low temperature measurement and surge current suppression. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0024] Example 1
[0025] A method for preparing a low-resistance negative temperature coefficient thermistor ceramic material comprises the following steps:
[0026] (1) Analytically pure copper acetate, cobalt acetate, manganese acetate and oxalic acid are used as raw materials, and the atomic percentages of Cu, Co and Mn are accurately weighed at 6.67%, 26% and 67.33% respectively, and oxalic acid is weighed at 1.1 times the total molar amount of metal atoms (Cu, Co and Mn). The mixture, grinding medium agate balls and dispersant anhydrous ethanol are charged into a ball mill at a weight ratio of 1:2:3 and ball milled (rotation speed is 250 r / min) for 5 hours to obtain a mixed powder;
[0027] (2) drying the mixed powder at 80° C. for 12 h, calcining at 800° C. for 2 h, cooling, ball milling (speed of 250 r / min) for 12 h, drying at 80° C., and filtering through an 80-mesh sieve to obtain a powder;
[0028] (3) Adding a binder (5 wt% polyvinyl alcohol solution) to the powder of step (2) for granulation, the mass ratio of the binder to the powder being 8:92, and then molding into a disc with a diameter of 10 mm at a pressure of 10 MPa. The formed body is calcined at 1100° C. for 3 h and finally cooled to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0029] 1) The prepared negative temperature coefficient thermistor ceramic material is subjected to an electrical performance test. The test method is as follows: the negative temperature coefficient thermistor ceramic material is first surface polished with corundum as the polishing medium, and then a uniform layer of silver paste is coated on both surfaces. After drying, the silver is burned at 750°C in a resistance furnace and kept warm for 15 minutes. The ceramic sample after silvering is polished on the side and then subjected to an electrical performance test.
[0030] Resistance measurement: The silver electrode lead is welded to the silvered ceramic sample. The resistance value is tested using an Agilent 34401A digital multimeter. The resistance R at 25°C and 85°C is measured in silicone oil. 25 and R 85 , calculate the resistivity according to the formula:
[0031]
[0032] Where: ρ is the resistivity of the sample, Ω·cm; R is the resistance of the sample, Ω; S is the area of the sample, cm 2 ; L is the thickness of the sample, cm.
[0033] B value calculation:
[0034]
[0035] Where R1 and R2 are the resistance values of the sample at 25°C and 85°C, respectively.
[0036] The electrical parameters of the negative temperature coefficient thermistor ceramic material prepared in this embodiment are measured as follows: room temperature resistivity is 993.8±1%Ω·cm, and B value is 3548±1%K.
[0037] 2) Aging value test: The negative temperature coefficient thermistor ceramic material prepared in this embodiment was placed in an oven at 150° C. for aging for 500 h, then taken out and the resistance value at 25° C. was measured in silicone oil. The aging value was calculated according to the following formula:
[0038] Aging value = (R1'-R1) / R1*100%
[0039] Wherein, R1 is the resistance value of the sample at 25°C, and R1' is the resistance value of the sample at 25°C after aging.
[0040] The aging value of the negative temperature coefficient thermistor ceramic material prepared in this embodiment is measured to be 2.68±0.1%.
[0041] Example 2
[0042] A method for preparing a low-resistance negative temperature coefficient thermistor ceramic material comprises the following steps:
[0043] (1) Analytically pure copper acetate, cobalt acetate, manganese acetate and oxalic acid are used as raw materials, and the atomic percentages of Cu, Co and Mn are accurately weighed at 10%, 22.67% and 67.33%, respectively. Oxalic acid is weighed at 1.5 times the total molar amount of metal atoms (Cu, Co and Mn). The mixture, grinding medium agate balls and dispersant anhydrous ethanol are placed in a ball mill at a weight ratio of 1:2:3, and the ball mill is rotated at a speed of 250 r / min for 5 hours to obtain a mixed powder;
[0044] (2) drying the mixed powder at 80° C. for 12 h, calcining at 700° C. for 2 h, cooling, ball milling (speed of 250 r / min) for 12 h, drying at 80° C., and filtering through an 80-mesh sieve to obtain a powder;
[0045] (3) Add a binder (5 wt% polyvinyl alcohol solution) to the powder of step (2) for granulation, wherein the mass ratio of the binder to the powder is 8:92, and then mold it into a disc with a diameter of 10 mm at a pressure of 10 MPa. The formed green body is calcined at 1000° C. for 3 h and finally cooled to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0046] The electrical parameters of the negative temperature coefficient thermistor ceramic material prepared in this embodiment are measured as follows: room temperature resistivity is 558.8±1%Ω·cm, and B value is 3288±2%K.
[0047] The aging value of the negative temperature coefficient thermistor ceramic material prepared in this embodiment was measured to be 4.08±0.1%.
[0048] Example 3
[0049] A method for preparing a low-resistance negative temperature coefficient thermistor ceramic material comprises the following steps:
[0050] (1) Analytically pure copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid are used as raw materials, and the atomic percentages of Cu, Co, Ni and Mn are accurately weighed at 6.67%, 26%, 6.66% and 60.67%, respectively. Oxalic acid is weighed at 1.5 times the total molar amount of metal atoms (Cu, Co, Ni and Mn). The mixture, grinding medium agate balls and dispersant anhydrous ethanol are charged into a ball mill at a weight ratio of 1:2:3 and ball milled (rotation speed is 250 r / min) for 5 hours to obtain a mixed powder;
[0051] (2) drying the mixed powder at 80° C. for 12 h, calcining at 800° C. for 2 h, cooling, ball milling (speed of 250 r / min) for 12 h, drying at 80° C., and filtering through an 80-mesh sieve to obtain a powder;
[0052] (3) Adding a binder (5 wt% polyvinyl alcohol solution) to the powder of step (2) for granulation, the mass ratio of the binder to the powder being 8:92, and then molding into a disc with a diameter of 10 mm at a pressure of 10 MPa. The formed body is calcined at 1100° C. for 3 h and finally cooled to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0053] The electrical parameters of the negative temperature coefficient thermistor ceramic material prepared in this embodiment are measured as follows: room temperature resistivity is 137.2±0.5%Ω·cm, and B value is 3222±1%K.
[0054] The aging value of the negative temperature coefficient thermistor ceramic material prepared in this embodiment was measured to be 2.97±0.1%.
[0055] Example 4
[0056] A method for preparing a low-resistance negative temperature coefficient thermistor ceramic material comprises the following steps:
[0057] (1) Analytically pure copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid are used as raw materials, and the atomic percentages of Cu, Co, Ni and Mn are accurately weighed at 6.67%, 26%, 13.33% and 54%, respectively. Oxalic acid is weighed at 1.1 times the total molar amount of metal atoms (Cu, Co, Ni and Mn). The mixture, grinding medium agate balls and dispersant anhydrous ethanol are charged into a ball mill at a weight ratio of 1:2:3 and ball milled (rotation speed is 250 r / min) for 5 hours to obtain a mixed powder;
[0058] (2) drying the mixed powder at 80° C. for 12 h, calcining at 700° C. for 2 h, cooling, ball milling (speed of 250 r / min) for 12 h, drying at 80° C., and filtering through an 80-mesh sieve to obtain a powder;
[0059] (3) Adding a binder (5 wt% polyvinyl alcohol solution) to the powder of step (2) for granulation, the mass ratio of the binder to the powder being 8:92, and then molding into a disc with a diameter of 10 mm at a pressure of 10 MPa. The formed body is calcined at 1100° C. for 3 h and finally cooled to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0060] The electrical parameters of the negative temperature coefficient thermistor ceramic material prepared in this embodiment are measured as follows: room temperature resistivity is 28.4±0.5%Ω·cm, and B value is 3062±1%K.
[0061] The aging value of the negative temperature coefficient thermistor ceramic material prepared in this embodiment is measured to be 2.75±0.1%.
[0062] Example 5
[0063] A method for preparing a low-resistance negative temperature coefficient thermistor ceramic material comprises the following steps:
[0064] (1) Analytically pure copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid are used as raw materials, and the atomic percentages of Cu, Co, Ni and Mn are accurately weighed at 6.67%, 26%, 13.33% and 54%, respectively. Oxalic acid is weighed at 1.5 times the total molar amount of metal atoms (Cu, Co, Ni and Mn). The mixture, grinding medium agate balls and dispersant anhydrous ethanol are charged into a ball mill at a weight ratio of 1:2:3 and ball milled (rotation speed is 250 r / min) for 5 hours to obtain a mixed powder;
[0065] (2) drying the mixed powder at 80° C. for 12 h, calcining at 700° C. for 2 h, cooling, ball milling (speed of 250 r / min) for 12 h, drying at 80° C., and filtering through an 80-mesh sieve to obtain a powder;
[0066] (3) Add a binder (5 wt% polyvinyl alcohol solution) to the powder of step (2) for granulation, wherein the mass ratio of the binder to the powder is 8:92, and then mold it into a disc with a diameter of 10 mm at a pressure of 10 MPa. The formed green body is calcined at 1200° C. for 3 h and finally cooled to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0067] The electrical parameters of the negative temperature coefficient thermistor ceramic material prepared in this embodiment are measured as follows: the room temperature resistivity is 28.0±0.5%Ω·cm, and the B value is 3056±1%K.
[0068] The aging value of the negative temperature coefficient thermistor ceramic material prepared in this embodiment was measured to be 2.65±0.1%.
[0069] Example 6
[0070] A method for preparing a low-resistance negative temperature coefficient thermistor ceramic material comprises the following steps:
[0071] (1) Analytically pure copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid are used as raw materials, and the atomic percentages of Cu, Co, Ni and Mn are accurately weighed at 6.67%, 26%, 16.66% and 50.67%, respectively. Oxalic acid is weighed at 1.5 times the total molar amount of metal atoms (Cu, Co, Ni and Mn). The mixture, grinding medium agate balls and dispersant anhydrous ethanol are charged into a ball mill at a weight ratio of 1:2:3 and ball milled (rotation speed is 250 r / min) for 5 hours to obtain a mixed powder;
[0072] (2) drying the mixed powder at 80° C. for 12 h, calcining at 700° C. for 2 h, cooling, ball milling (speed of 250 r / min) for 12 h, drying at 80° C., and filtering through an 80-mesh sieve to obtain a powder;
[0073] (3) Add a binder (5 wt% polyvinyl alcohol solution) to the powder of step (2) for granulation, wherein the mass ratio of the binder to the powder is 8:92, and then mold the powder into a disc with a diameter of 10 mm at a pressure of 10 MPa. The formed green body is calcined at 1150° C. for 3 h and finally cooled to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
[0074] The electrical parameters of the negative temperature coefficient thermistor ceramic material prepared in this embodiment are measured as follows: the room temperature resistivity is 38.8±0.5%Ω·cm, and the B value is 3071±1%K.
[0075] The aging value of the negative temperature coefficient thermistor ceramic material prepared in this embodiment was measured to be 2.38±0.1%.
Claims
1. A low resistance negative temperature coefficient thermistor ceramic material and a preparation method thereof, characterized in that: The steps include: (1) mixing copper acetate, cobalt acetate, nickel acetate, manganese acetate and oxalic acid uniformly to obtain a mixture, and then adding the mixture, a grinding medium and a dispersant into a ball mill to perform ball milling to obtain a mixed powder; (2) drying the mixed powder of step (1), calcining it, cooling it, ball-milling it for a second time, drying it, and sieving it to obtain a powder; (3) Adding a binder to the powder of step (2) to granulate, then performing compression molding, calcining the molded body, and finally cooling to obtain a low-resistance negative temperature coefficient thermistor ceramic material.
2. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (1), the amounts of copper acetate, cobalt acetate, nickel acetate and manganese acetate are measured according to the atomic percentage of metals, wherein the atomic percentage of copper is 6.67-10%, the atomic percentage of cobalt is 22.67-26%, the atomic percentage of nickel is 0-16.66%, and the atomic percentage of manganese is 50.67-67.33%, and the amount of oxalic acid is 1-1.5 times the total molar amount of metal atoms.
3. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (1), the dispersant is anhydrous ethanol; and the weight ratio of the mixture, the grinding medium and the dispersant is 1:(1-3):(1-3).
4. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (1), the rotation speed of the ball mill is 200 to 300 r / min, and the ball milling time is 3 to 12 h.
5. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (2), the drying temperature is 80° C. and the drying time is 12 to 24 hours.
6. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (2), the calcination temperature is 600-900° C. and the calcination time is 2-4 hours.
7. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (2), the rotation speed of the secondary ball milling is 200 to 300 r / min, and the time is 6 to 24 hours.
8. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (3), the binder is a polyvinyl alcohol solution with a concentration of 5 to 8 wt%, and the mass ratio of the binder to the powder is (5 to 8): (92 to 95).
9. The method for preparing the low resistance negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: In step (3), the calcination temperature is 1000-1200° C. and the calcination time is 3-8 hours.
10. A low-resistance negative temperature coefficient thermistor ceramic material prepared by the method for preparing a low-resistance negative temperature coefficient thermistor ceramic material as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Negative temperature coefficient two-phase composite thermistor composition and preparation thereof
CN101328062A
Method for preparing thin-film NTC thermistor
CN107117991A
Quaternary system negative temperature coefficient heat sensitive resistance material and preparation method thereof
CN109516781A
Preparation method of copper-containing negative temperature coefficient thermal sensitive ceramic material
CN115073140A
Thermistor, product of the same, and system
JP2020167332A
